ROBOTICS AND ARTIFICIAL INTELLIGENCE TRAINING FOR STUDENTS IN INTENSIF TARUNA PEMBANGUNAN SENIOR HIGH SCHOOL SURABAYA - Agustin, Eva Inaiyah; Nahdliyah, Sisca Dina Nur; Putri, Tesa Eranti; Prihasty, Wilda; Tunggadewi, Elsyea Adia; Arifianto, Deny; Wardhana, Ananthyo Whisnu (Universitas Airlangga, 2025)
Artificial Intelligence is a new science that is currently being widely developed and used in all aspects to solve various tasks and problems. In advanced robotics systems, AI is used in robots to understand, reason, and act autonomously in complex environments. So far, partners still borrow robots from other agencies during robotics extracurricular activities. This community service activity aims to introduce Artificial Intelligence (AI) and robotics technology to high school students and hone students' skills and can develop extracurricular robotics. This activity is in the form of training that begins with providing material on the topic of AI and robotics. This training began with providing AI and robotics materials attended by 30 students and took place in the computer laboratory of SMA Intensive Taruna Pembangunan Surabaya (SMA ITP Surabaya). The robot used is an arm robot, a robot that is often used in industry for various tasks. To determine the increase in knowledge and skills, pre-test and post-test methods are carried out before and after the training and case studies/projects are provided at the end of the training. There was an increase in student knowledge of 18.77% and student skills as evidenced by all (10) groups being able to move the target. With this activity, SMA ITP Surabaya has a robotics module in the form of an arm robot and is able to develop and increase student interest in robotics extracurricular activities.